Grandmultiparity, Maternal Age, and the Risk for Uterine Rupture—A Multicenter Cohort Study. Issue 4 (December 2020) - Hochler, H.; Wainstock, T.; Lipschuetz, M.; Sheiner, E.; Ezra, Y.; Yagel, S.; Walfisch, A.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:267–273) The rare complication of uterine rupture can potentially result in catastrophic consequences for both mother and fetus. The most common risk factor for uterine rupture is previous cesarean delivery (CD), but few published studies exist addressing uterine rupture in women without a history of previous CD. Conflicting conclusions have been reported regarding any association between grandmultiparity and uterine rupture. In this population, obstetricians have been cautious due to a fear of increased risk for uterine rupture. This approach might trigger the performance of unnecessary CDs. Therefore, this study was undertaken to determine if grandmultiparity is an independent risk factor for intrapartum uterine rupture in women without a history of previous uterine surgery.